If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(3h + -7) = 76 Reorder the terms: 2(-7 + 3h) = 76 (-7 * 2 + 3h * 2) = 76 (-14 + 6h) = 76 Solving -14 + 6h = 76 Solving for variable 'h'. Move all terms containing h to the left, all other terms to the right. Add '14' to each side of the equation. -14 + 14 + 6h = 76 + 14 Combine like terms: -14 + 14 = 0 0 + 6h = 76 + 14 6h = 76 + 14 Combine like terms: 76 + 14 = 90 6h = 90 Divide each side by '6'. h = 15 Simplifying h = 15
| 3x+(-3x)=5 | | 2+3x+4-1= | | 0.16y+0.08(y+9000)=2400 | | 6(t-3)+4t=5(2t+5)-13 | | .11x-400-.03x=840 | | 4x+6+3x+4=(-40)+4 | | 3z-836=-77 | | Y+8=2y-4 | | -3x+10=94+4x | | 5y^2-7y=-2 | | 27=3(2x-7) | | -11x-400-.03x=840 | | 27=15+9 | | 3x-9=5x+2 | | -1.08=0.9v | | 2x+2y=2x+9 | | 4x^2-8x+4y^2+12y-131=0 | | 6s+2=-10 | | K-7+6= | | 12n-17n+6=32 | | v^2-4vx-12x^2=0 | | 3x(2)=12+5x | | 96=16+2x | | 9(t-6)+3=6(2t+3)-9 | | (17b-5)-4(4b+4)=-6 | | (X^2+4)=25 | | 2a+8a=8 | | (2x-4)-(5x+3)= | | 4c-43=7c-193 | | 44=4(x-5) | | -43=2+9x | | 3(y-7)=2(4+y) |